Characterization of red pigmented yeasts and genes associated with astaxanthin synthesis in Rhodotorula mucilaginosa HL26-1 and Rhodotorula paludigena LL69-1 - Patcharaporn Hoondee; Nisachon Tedsree; Sukanya Phuengjayaem; Engkarat Kingkaew; Boonchoo Sritularak; Pornchai Rojsitthisak; Takuji Nakashima; Worathat Thitikornpong; Somboon Tanasupawat (F1000Research, 2025)
Background Astaxanthin, a red xanthophyll carotenoid, is a powerful antioxidant, anticancer, and glucose and lipid homeostasis regulator. Some pigmented yeasts belonging to the genus Rhodotorula , the well-known yeast for beta-carotene production, have been reported as natural astaxanthin producers. However, the lack of genomic data on astaxanthin-producing strains within these species hinders the identification of biosynthetic routes, molecular characterization of these pathways, and gene editing applications. Methods This study explored the diversity and astaxanthin production capability of cultivable pigmented yeast in flower samples. The astaxanthin production ability was inspected by three consecutive methods, including thin-layer chromatography (TLC) for the preliminary step, followed by quantitative spectrophotometry and high-performance liquid chromatography (HPLC) for qualitative validation. The draft genome sequence and astaxanthin-producing genes of astaxanthin-producing yeasts were examined. Results Twelve of 23 yeasts from floral samples exhibited natural pigmentation, with colors ranging from pinkish-orange to red, and exhibited the potential for astaxanthin synthesis. These yeasts were Rhodotorula paludigena (three strains) and Rhodotorula mucilaginosa (nine strains). Among R. mucilaginosa strains, HL26-1 had the greatest astaxanthin content (104.98 ± 0.13 μg/g DCW) and yield (0.9280 ± 0.0012 mg/L). Strain LL69-1 has the greatest astaxanthin content (275.94 ± 0.16 μg/g DCW) and yield (1.8632 ± 0.0023 mg/L) among R. paludigena strains. The 18.78 Mbp R. mucilaginosa HL26-1 genome includes 5,711 protein-coding genes. Conversely, the R. paludigena LL69-1 genome was 20.99 Mbp, encompassing 6,782 predicted genes. A comprehensive investigation of draft genome sequences of these two strains identified CrtE , CrtYB , CrtI , CrtS , and CrtR as potential astaxanthin transcription genes. Conclusion Here, our results highlight the outstanding potential of two naturally pigmented yeasts, R. mucilaginosa HL26-1 and R. paludigena LL69-1, for astaxanthin production. Furthermore, our findings provide information on the whole genome and protein-encoded genes associated with astaxanthin production, which serve as valuable biological resources for various biotechnological applications.
Keywords: Antioxidant Activity and Oxidative Stress; Protein Hydrolysis and Bioactive Peptides; Algal biology and biofuel production